2014
DOI: 10.1007/s00345-014-1427-x
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic radiotherapy for isolated nodal recurrence of prostate cancer

Abstract: Our experience shows that SBRT for isolated nodal relapse from prostate cancer is a safe treatment, with promising results in terms of efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 25 publications
1
50
1
Order By: Relevance
“…In this context, data on ADT‐FS were assessed. Despite only five studies having shown clear results, the data suggest SBRT could defer ADT for a median time of about 1–3 years, consistently with PFS …”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…In this context, data on ADT‐FS were assessed. Despite only five studies having shown clear results, the data suggest SBRT could defer ADT for a median time of about 1–3 years, consistently with PFS …”
Section: Discussionmentioning
confidence: 92%
“…The exclusion reasons with references are listed in Data S2. Finally, 14 articles were selected for data extraction and subsequent qualitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations